Distance Learning as a Factor of Creating Wide Opportunities (Journal of Pedagogical Inventions and Practices, 2022)
In the article, distance learning technology is a goal-oriented interactive process of interaction between learners and teachers with each other and with teaching aids, while the learning process does not depend on their geographical spatial location. The educational process consists of sub-systems, ie a specific pedagogical system that includes elements such as the purpose, content, methods, tools, organizational forms, control, educational, financial-economic, normative-legal and marketing, the direct production process of educational technologies analysis of scientific sources on the use of distance learning in the development of students' learning competencies, competency qualities, learning competencies , the essence of the concepts of distance learning, models of distance learning, principles, stages of implementation of distance learning, the content of the requirements for distance learning are analyzed.